Optoelectronic and material properties of solution-processed Earth-abundant Cu2BaSn(S, Se)4 films for solar cell applications. (February 2021) - Teymur, Betul; Levcenco, Sergiu; Hempel, Hannes; Bergmann, Eric; Márquez, José A.; Choubrac, Leo; Hill, Ian G.; Unold, Thomas; Mitzi, David B.
Abstract: Copper barium thioselenostannate, Cu2 BaSnS4− x Se x (CBTSSe), absorbers employ low-toxicity and abundant metals while offering low-cost manufacturing options, controllable stoichiometry and band gap tunability (from 2 eV at x = 0 to 1.55 eV at x = 3). CBTSSe can therefore be considered a prospective candidate for maintaining or improving upon the advantages of already commercialized Cu(In, Ga)(S, Se)2 (CIGSSe) and CdTe absorbers. In this study, we focus on solution-deposited stoichiometric CBTSSe films with band gap of 1.59 eV ( x ≈ 3) and explore the fundamental film properties. Temperature- and excitation-dependent photoluminescence studies reveal a dominant defect emission at 1.5 eV and a second deep defect feature at 1.15 eV. From time-resolved terahertz measurements, we find a charge carrier (electron and hole sum) mobility of 140 cm 2 /Vs—i.e., comparable to values in CIGSSe or Cu2 ZnSnS4− x Se x (CZTSSe)—as well as a two-component minority carrier lifetime. A longer-lived lifetime component ( 2 ns) arises from bulk recombination. However, strong recombination at the (bare) surface leads to a 50 ps lifetime, inferior to state-of-the-art CIGSSe or CZTSSe absorbers. This recombination issue may worsen for CBTSSe/CdS interfaces, due to a cliff-like band alignment with 0.6 eV band offset, as revealed by ultraviolet photoemission spectroscopy. A low number of charge carriers within the absorber further contributes to a high series resistance. Employing these films, we also report the highest performance achieved from solution-processed trigonal CBTSSe thin-film photovoltaic devices, with open circuit voltage, short-circuit current density, fill factor and efficiency of 470 mV, 14.3 mA/cm 2, 43.6% and 2.9%, respectively. The physical measurements provided on the solution-processed CBTSSe absorber further point to critical areas for future improvement of CBTSSe and related photovoltaic cells in the quest for higher efficiency devices based on earth abundant metals. Graphical Abstract: ga1 Highlights: The temperature-dependent PL in CBTSSe shows a shallow donor ( 30 meV) and acceptor ( 70 meV) as well as a deep acceptor ( 0.4 eV). CBTSSe films suffer from surface recombination with a bare film surface-dominated lifetime of 50 ps measured from THz spectroscopy. UPS shows cliff-like band alignment with 0.6 eV conduction band offset at the junction of CdS and CBTSSe. Solution-processed CBTSSe PV efficiency of 2.93% has been achieved, with limitations notably from V OC loss.